2020
DOI: 10.1007/s10912-020-09657-z
|View full text |Cite
|
Sign up to set email alerts
|

A Look Back and a Path Forward: Poetry's Healing Power during the Pandemic

Abstract: This discussion seeks to highlight the ability of poetry to combat loneliness, a growing public health problem with significant negative health outcomes that potentially impact millions of Americans. We argue that poetry can play a very relevant role and have an impact in medicine. Through a brief literature review of previous studies on poetry in medicine, we demonstrate that poetry can not only combat loneliness but can also play important roles in helping patients, physicians, and other healthcare professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Most importantly, the accessible nature of poetry makes it an incredibly relevant and applicable tool, especially now, when genuine connections are a scarce commodity [28] . However, this reflection on ethics and the health crisis corresponds to the argument about social illness in times of the COVID-19 pandemic, focusing the narration or dis-course on contemporary art.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the accessible nature of poetry makes it an incredibly relevant and applicable tool, especially now, when genuine connections are a scarce commodity [28] . However, this reflection on ethics and the health crisis corresponds to the argument about social illness in times of the COVID-19 pandemic, focusing the narration or dis-course on contemporary art.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 More recently, Xiang et al underscored the use of poetry in providing psychological support to people during the Covid-19 pandemic. 42 On the other hand, nurses frequently seek knowledge of biomedical ethics to relieve moral distress, confusion, and psychological stress. 43 It seems that imparting moral knowledge by poetry is associated with diminished psychological stress and facilitated communication with patients, which makes them more sensitive to the observance of ethical principles and patients' rights.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated the importance of using poetry therapy by health professionals in a health promotion program for health education in another study [83]. In another study, it was reported that poetry therapy is an effective method to eliminate Art Therapy with the Extent of Health Promotion DOI: http://dx.doi.org/10.5772/intechopen.105368 the loneliness in society and to establish social interaction between individuals during pandemic periods [84].…”
Section: Poetry Therapymentioning
confidence: 99%